Trust, transparency and welfare: Third-sector adult social care delivery and the COVID-19 pandemic in the UK - Paul Chaney; Christala Sophocleous (Journal of Risk and Financial Management, 2021)
Since the move to quasi-federalism in the 1990s, different territorial welfare mixes on adult social care (ASC) have emerged in the four nations of the UK. This study explores policy actors' views on their effectiveness in the pandemic with reference to the role of institutions, trust and transparency. The analysis is based on extensive secondary data analysis and primary interviews with key individuals involved in the delivery and regulation of ASC. The findings highlight how the pandemic exposed existing pathologies and the need for reform in all four systems. Notably, the analysis shows how the present market-based tendering systems for allocating ASC contracts undermine inter-personal and institutional trust and compromise care quality. The wider significance of this lies in showing the pivotal role of trust during the emergency and that post-pandemic welfare reform needs to embed trust-building measures to deliver effective care.
Keywords: 330; pandemic; social welfare; trust; transparency; adult social care; UK